The newly industrializing countries of Asia - Tan, Gerald (Times Academic Press, 1995)
The Newly Industrializing Countries of Asia (NICs), which comprise Hong Kong, Singapore, South Korea and Taiwan, have been some of the fastest growing economies in the world since the 1960s. This book presents a comparative analysis of these achievements, in the light of analytical debates in the development economics studies. The factors that explain their emergence, and the role played by Japan are analyzed. The prospects of the Asian NICs in the increasingly hostile international economic environment of the 1990s and beyond are examined. Revised and updated, this new edition takes into account the momentous changes that have hit them more recently, including the Asian currency crisis.